Seleksi Tenaga Kerja (Pegawai) dalam Pendidikan Islam - Linda, Reflinda; Maharni, Septi; Jamilus, Jamilus (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to understand the Islamic perspective on workforce (employee) selection. This research uses a literature study approach (library research). Data collection was conducted through academic databases such as Google Scholar and Garuda using the keywords: “workforce selection,” “employee recruitment,” “Islamic education,” “Islamic HR management,” and “Islamic human resource management.” Purposive sampling technique was used to directly select literature that is relevant to the study focus. Data analysis was carried out using content analysis techniques. The analysis results indicate that from the perspective of Islamic teachings, the approach to recruitment and selection emphasizes values such as professional competence, relevant experience, honesty, piety, and noble character, as outlined in the Qur'an and the Prophet's hadiths. The implementation of this process must be conducted with full transparency, objectivity, and free from any form of favoritism or nepotism, in order to produce educators who are not only experts in their fields but also possess high integrity. Furthermore, this article explains that the use of systematic selection criteria, the application of advanced technology, and active participation from various relevant parties are strategic steps to ensure that the recruited educators truly meet the institution's needs